A Repeatable and Reproducible Digital Method to Quantify the Cement Excess and Enamel Loss after Debonding Lingual Multibracket Appliance Therapy - Alba Belanche Monterde; Alberto Albaladejo Martínez; Alfonso Alvarado Lorenzo; Adrián Curto; Jorge Alonso Pérez-Barquero; Clara Guinot-Barona; Álvaro Zubizarreta-Macho (Applied Sciences, 2021)
The aim of the present study is to present a repeatable, reproductible, and accurate morphometric measurement method for measuring and quantifying the area and volume of cement that remains after fixed lingual multibracket appliance debonding, enamel loss after fixed lingual multibracket appliance debonding, and the volume of cement used to adhere fixed lingual multibracket appliances. Ten conventional lingual brackets were cemented in 10 extracted teeth embedded into an epoxy resin model simulating a dental arch. This model was scanned before and after bonding the lingual brackets, after debonding, and after polishing the surfaces. We also performed a Micro-Computed Tomography scan of the lingual brackets used. Afterward, the standard tessellation language (STL) digital file was aligned, each tooth was segmented individually, and the file was re-aligned using engineer morphometry software. Inter-operator and intra-operator comparative analyses were performed using the ANOVA test, and the repeatability and reproducibility of the morphometric measurement technique were analyzed using Gage R&R statistical analysis. Repeatability showed 0.07% and 0.16% variability associated with the area and volume measures, respectively, while reproducibility showed 0.00% variability associated with the area and volume measures, respectively. In conclusion, the morphometric measurement technique is a repeatable, reproductible, and accurate morphometric measurement method for quantifying the area and volume of cement that remains after fixed lingual multibracket appliance debonding, enamel loss after fixed lingual multibracket appliance debonding, and the volume of cement used to adhere fixed lingual multibracket appliances.